Validity and reliability test of School web site evaluation scale in terms of contribution to school-family communication level in preschool period - Topaloglu, Aysegul Ozdemir; Celikoz, Nadir (UNIV GRANADA, FAC CIENCIAS EDUCACION, 2018)
This study was conducted to emphasize the importance of school-parent communication by developing a web-based model that was used and evaluated by both parents and teachers. The study was conducted in the Kesan District in Edirne Province with 32 teachers who work for the Ministry of Education's independent kindergartens and 31 parents who provided feedback. A scale was developed in two forms-one for teachers and another for parents-to discover whether the internet-based web model positively affected school-parent communication. During the development of the scale, pre-interviews were held with teachers and parents who could be accessed. Then, which programs/software to be integrated into the web design that will include open-ended questions in order to improve the school-parent communication. A 35-question interview form was generated according to the results of the pre-interviews and the open-ended questions. In the light of expert opinion, the teacher form of the scale included eight questions that asked for personal information and 31 articles, 23 of which likert-type were, while the parent form included six questions requesting personal information and 29 articles, 23 of which were Likert-type. Factor and article loadings, averages, standard deviation, total article correlation, and correlation coefficients between subtests were calculated for both tests. The coefficient of reliability for the teacher form was found to be Cronbach a=.89 and Cronbach a=.97 for the parent form. After the results were obtained through analysis, factor analysis was applied to the 31-article teacher form and the 29-article parent form to determine the construction validity and a two-factor scale was obtained. The results of the study show that the scale is highly valid and reliable
Keywords: School-parent communication; Web-based model; Scale; Factor analysis; Education & Educational Research